Lithofacies palaeogeography as a guide to petroleum exploration - Feng Zengzhao (Journal of Palaeogeography, 2013)
Lithofacies palaeogeography as a guide to petroleum exploration is a very important topic. By using the following five exploration examples, this paper discusses the guide of lithofacies palaeogeography or of sedimentary facies to petroleum exploration. These examples include the dolostone of the Lower Ordovician Majiagou Formation 5 in the Ordos area, the Donghe Sandstone of the Upper Devonian and Lower Carboniferous in the Tarim Basin, the reef of the Upper Permian Changxing Formation in the Sichuan Basin, the oolitic bank of the Lower Triassic Feixianguan Formation in the Sichuan Basin, and the lacustrine delta sediments and gravity flow sediments of the Middle and Upper Triassic Yanchang Formation in the Ordos Basin.